Justice denied : exploring inequities in the legal system - Johnston, Ed; Smyth, Claire-Michelle (Routledge contemporary issues in criminal justice and procedure., 2026)
"This volume focuses on injustice in the Criminal Justice System in England and Wales and presents a discussion around the barriers faced to achieving justice. The book draws on contributions from established and emerging scholars, as well as insight from professional practice to provide insight into the contemporary challenges in distinct areas of injustice through original analysis and argument. Topics covered include the theory of punishment, criminal justice, access to justice, climate justice, migrant justice and barriers to justice. The volume will be of interest to researchers, academics and policy-makers working in the areas of Criminal Law, Criminology, Sociology of Law and Human Rights Law. Focused on the legal system of England and Wales, the issues raised are relevant for an international readership"-- Provided by publisher.